Microrobotics and Microorganisms: Biohybrid Autonomous Cellular Robots - Alapan, Yunus; Yasa, Oncay; Yigit, Berk; Yasa, I. Ceren; Erkoc, Pelin; Sitti, Metin (Annual Review of Control, Robotics, and Autonomous Systems, 2019)
Biohybrid microrobots, composed of a living organism integrated with an artificial carrier, offer great advantages for the miniaturization of devices with onboard actuation, sensing, and control functionalities and can perform multiple tasks, including manipulation, cargo delivery, and targeting, at nano- and microscales. Over the past decade, various microorganisms and artificial carriers have been integrated to develop unique biohybrid microrobots that can swim or crawl inside the body, in order to overcome the challenges encountered by the current cargo delivery systems. Here, we first focus on the locomotion mechanisms of microorganisms at the microscale, crucial criteria for the selection of biohybrid microrobot components, and the integration of the selected artificial and biological components using various physical and chemical techniques. We then critically review biohybrid microrobots that have been designed and used to perform specific tasks in vivo. Finally, we discuss key challenges, including fabrication efficiency, swarm manipulation, in vivo imaging, and immunogenicity, that should be overcome before biohybrid microrobots transition to clinical use.
Keywords: bacteria